2021
DOI: 10.1038/s41598-021-90904-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to metals and morbidity at eight years follow-up in women of childbearing age

Abstract: This exploratory study was aimed to investigate the link between toxic metal content in women’s urine and their morbidity 2 years before and 6 years after the test. Concentrations of 25 metals in urine were analyzed for 111 pregnant women collected prior to delivery. All women were of Arab-Bedouin origin. Information on primary care and hospital visits during the study period was obtained. In a Poisson regression model, a health outcome was regressed over metal exposure and other factors. A Weighted Quantile S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Positive correlation between toxic elements, e.g. Al and Ni, observed in our study may be the consequence of exposure to environmental concomitants 21 . Correlation index values are higher for AF with chromosomal abnormalities which may be related to the exposure of pregnant women in this group to different toxic elements during pregnancy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Positive correlation between toxic elements, e.g. Al and Ni, observed in our study may be the consequence of exposure to environmental concomitants 21 . Correlation index values are higher for AF with chromosomal abnormalities which may be related to the exposure of pregnant women in this group to different toxic elements during pregnancy.…”
Section: Discussionsupporting
confidence: 56%
“…Correlation index values are higher for AF with chromosomal abnormalities which may be related to the exposure of pregnant women in this group to different toxic elements during pregnancy. It was found that toxic elements such as Cd, Ni and Al are adversely related to chronic morbidity 21,22 . Results of the study by McLachlan et al 23 suggest that aluminium accumulation in the brains of patients with Alzheimer's disease and Down's Syndrome may contribute to the neuropathology of those neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…↑ [590,592] ↑A [591,592] Permethrin ↑ [594,596] ↑A [594] ↑A [594] Parabens ↑ [459,614,615] ↑D [616] ↑D [616] ↑D [616,740] Tween-80 ↑A [618] ↑A [618] CMC ↑A [618] ↑A [618] (continued on next page) Cadmium ↓ [634] ↑D [188,632] ↑D [632] ↑A [189] ↑D [632] ↑A [189] ↑D [188] ↓D [480] ↓C [463] ↓A [463,636] ↔A [635] Arsenic ↓, [638,639] ↑D [640,641] ↓A [642] ↓A [642] ↔A [642] ↔D,C [208] DBTs ↑ [371,364] ↑D [364] ↔D [388] Fructose, HFCS ↑A [703] ↑A [703] ↑C [610] ↑C [610] βHCH ↑D…”
Section: Neonicotinoid Pesticidesmentioning
confidence: 99%
“…The PECO criteria were used to guide title and abstract screening, and 3192 studies were excluded, leaving 30 for full text screening. Of these, three studies were excluded because the metal exposures were not measured at the individual level [35,36] or definitions for the cardiovascular risk factors or outcomes were not consistent with the other studies included [37]; two additional studies [38,39] were identified via manual search or reference lists of the included studies. We also found two potentially eligible studies but did not include them in this review because mixed-effects regression models, not multipollutant approaches considered in this review, were used among the study population stratified by baseline metal concentrations to estimate joint associations of metal mixtures with blood and pulse pressure trajectories [40] or the clusters identified from a multi-pollutant approach were not linked to CVD-related outcomes [41].…”
Section: Resultsmentioning
confidence: 99%
“…The PECO criteria were used to guide title and abstract screening, and 3192 studies were excluded, leaving 30 for full text screening. Of these, three studies were excluded because the metal exposures were not measured at the individual level [ 35 , 36 ] or definitions for the cardiovascular risk factors or outcomes were not consistent with the other studies included [ 37 ]; two additional studies [ 38 , 39 ] were identified via manual search or reference lists of the included studies.…”
Section: Resultsmentioning
confidence: 99%